10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Adults with intellectual disabilities experience significantly worse health outcomes and die younger than people without intellectual disability. People with severe or profound intellectual disability have particularly complex health needs. However, no large-scale population-based studies have specifically examined mortality patterns and factors associated with age at death in this group. This population-based study used data from the English Learning from Lives and Deaths (LeDeR) mortality review programme and the Office for National Statistics (ONS) between 2021 and 2023. We included 1,301 adults with severe or profound intellectual disability, 2,626 adults with mild or moderate intellectual disability, and 536,311 adults from the general population. We collected sociodemographic, clinical, and mortality data. Key outcomes included co-occurring conditions, age at death, causes of death, avoidable mortality, and years of life lost. We used Cox regression and multiple linear regression to examine factors associated with age at death. We defined avoidable deaths as deaths before the age of 75 years due to preventable or treatable causes and adjudicated them by mapping the underlying cause of death to the Organisation for Economic Co-operation and Development (OECD) list of avoidable causes of death. Adults with severe or profound intellectual disability had a significantly higher prevalence of dysphagia (63.0%), epilepsy (36.1%) and visual problems (35.9%) compared with those with mild or moderate intellectual disability (p < 0.01 for each). The median age at death was markedly lower in this group (57.9 years) compared to those with mild or moderate intellectual disability (65.0 years) and the general population (81.9 years) (p < 0.001). We classified two-fifths of deaths among adults with severe or profound intellectual disability as avoidable (39.5%), resulting in 15,059.4 years of life lost. Severe or profound intellectual disability was associated with a younger age at death (adjusted mean difference -7.17 years; 95% confidence interval [CI] [-8.16, -6.18]; p < 0.001). A key limitation is that the cohort was restricted to mortality data, meaning our findings reflect factors associated with age at death rather than mortality risk. Our findings highlight the urgent need for tailored public health strategies, early interventions, and integrated care models to improve clinical outcomes for individuals with severe and profound intellectual disability.